Negative-energy Waves in the Vertical Threads of a Solar Prominence - Jincheng Wang; Dong Li; Chuan Li; Yijun Hou; Zhike Xue; Zhe Xu; Liheng Yang; Qiaoling Li (The Astrophysical Journal Letters, 2024)
Solar prominences, intricate structures on the Sun’s limb, have been a subject of fascination owing to their threadlike features and dynamic behaviors. Utilizing data from the New Vacuum Solar Telescope, Chinese H α Solar Explorer, and Solar Dynamics Observatory, this study investigates the transverse swaying motions observed in the vertical threads of a solar prominence during its eruption onset on 2023 May 11. The transverse swaying motions were observed to propagate upward, accompanied by upflowing materials at an inclination of 31° relative to the plane of the sky. These motions displayed small-amplitude oscillations with corrected velocities of around 3–4 km s ^−1 and periods of 13–17 minutes. Over time, the oscillations of swaying motion exhibited an increasing pattern in displacement amplitudes, oscillatory periods, and projected velocity amplitudes. Their phase velocities are estimated to be about 26–34 km s ^−1 . An important finding is that these oscillations’ phase velocities are comparable to the upward flow velocities, measured to be around 30–34 km s ^−1 . We propose that this phenomenon is associated with negative-energy wave instabilities, which require comparable velocities of the waves and flows, as indicated by our findings. This phenomenon may contribute to the instability and observed disruption of the prominence. By using prominence seismology, the Alfvén speed and magnetic field strength of the vertical threads have been estimated to be approximately 21.5 km s ^−1 and 1–3G, respectively. This study reveals the dynamics and magnetic properties of solar prominences, contributing to our understanding of their behavior in the solar atmosphere.